2019
DOI: 10.1080/09540121.2019.1623374
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers affecting PrEP adherence among Thai men who have sex with men (MSM) in the HPTN 067/ADAPT Study

Abstract: The HPTN 067/ADAPT Study evaluated the feasibility, acceptability and patterns of adherence and coverage for three randomly assigned oral FTC/TDF pre-exposure prophylaxis (PrEP) dosing regimens to prevent HIV infection: daily, time-driven (twice a week with a post-sex dose), and event-driven (pre/post-sex dosing). Using qualitative methods, we explored facilitators and barriers for each regimen among a subset of men who have sex with men (MSM) participants in Bangkok, Thailand. Between August 2013 and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
2
22
1
3
Order By: Relevance
“…This may suggest that individuals who perceive themselves at risk are more likely to keep accessing PrEP. This is consistent with previous research that concluded that PrEP use is driven by risk perceptions for HIV (Chemnasiri et al., 2020; Gombe et al., 2020; Liu et al., 2014). Regular STI testing is recommended as a key component of PrEP care and could lead to faster diagnoses of STIs among high‐risk groups (Werner et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may suggest that individuals who perceive themselves at risk are more likely to keep accessing PrEP. This is consistent with previous research that concluded that PrEP use is driven by risk perceptions for HIV (Chemnasiri et al., 2020; Gombe et al., 2020; Liu et al., 2014). Regular STI testing is recommended as a key component of PrEP care and could lead to faster diagnoses of STIs among high‐risk groups (Werner et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These include fear of needles stopping patients from getting requisite bloodwork to start and continue on PrEP and stigma in disclosing accurate sexual health history (though because a large proportion came to the clinic seeking PrEP these concerns were not necessarily observed in our sample). Combatting stigma is an ongoing issue in PrEP uptake and delivery (Chemnasiri et al., 2020; Knight et al., 2016; Liu et al., 2014; St. Vil et al, 2019). Stigma has been identified as one factor in decreased ART adherence for younger gbMSM (Tanner et al., 2016) as well as precarious employment, housing instability, substance abuse, and sexual identity issues (Eastwood & Birnbaum, 2007), which may help explain the significance of age in PrEP discontinuation in this study and others (Dolbecki‐Lewis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, only two items were related to intention and willingness to use PrEP: the degree of difficulty in taking the medication and attending the monitoring appointment. This finding conveyed the significance of adherence to treatment and access to healthcare as facilitators of PrEP use [ 22 , 23 ]. This is not a surprising result, as access to treatments, care, and HIV prevention in Colombia is fragmented, limited, and problematic due to the organization of its health system [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individual, societal, and systemic level facilitators and barriers to PrEP adherence among Thai YMSM identified in this study have also been reported in other studies of MSM and YMSM in the United States, Thailand, and other countries. Consistent with other studies [ 7 , 41 - 45 ], adherence facilitators included awareness of HIV risk and desire to protect themselves, concerns related to sexual partners, support from friends, sexual partners, family members, and adolescent-friendly providers, and PrEP affordability (PrEP is provided free of charge through universal health coverage for key populations in Thailand). Key barriers, also identified in other studies [ 41 - 44 , 46 - 49 ], included sexuality, HIV and PrEP stigma, attending regular PrEP medical appointments, forgetting to take PrEP daily or while intoxicated, not having PrEP with them at certain times, running out of PrEP, side effects, and low HIV risk perception.…”
Section: Discussionmentioning
confidence: 88%